2001
DOI: 10.3354/meps220179
|View full text |Cite
|
Sign up to set email alerts
|

Trophic interaction between copepods and ciliates: effects of prey swimming behavior on predation risk

Abstract: The transfer of matter and energy in planktonic food webs is determined by the encounter rate between predators and prey and subsequent attack and capture success. We tested if differences in swimming behavior and escape ability of 2 planktonic ciliates could explain differences in their susceptibility to predation from the calanoid copepod Acartia clausi. We chose 2 similarly sized ciliates, which exhibited very different swimming behavior: Strobilidium spiralis (Strobilidiina) and Metacylis sp. (Tintinnina).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 17 publications
3
46
1
Order By: Relevance
“…Alternative explanations for the threefold reduction in the predation rate (Table 2) include morphological differences or differences in swimming behavior (Broglio et al 2001). The free-swimming Eutintinnus sp.…”
Section: Prey Species Behaviormentioning
confidence: 99%
“…Alternative explanations for the threefold reduction in the predation rate (Table 2) include morphological differences or differences in swimming behavior (Broglio et al 2001). The free-swimming Eutintinnus sp.…”
Section: Prey Species Behaviormentioning
confidence: 99%
“…swimming along a curved spiral trajectory; Svensen & Kiørboe 2000, Broglio et al 2001; (3) the prey may switch its swimming behavior (e.g. Kerfoot 1978, Fields & Yen 1997; and (4) the predator may also switch its swimming behavior (e.g.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…A small number of laboratory studies have clearly demonstrated effects of prey motility on copepod predator detectability and/or encounter rates with various zooplankters as prey; i.e. nauplii (Titelman 2001), copepods (Kerfoot 1978, Tiselius et al 1997, cladocerans (Kerfoot 1978) and ciliates (Broglio et al 2001).…”
Section: Introductionmentioning
confidence: 99%